CONVERSATIONAL MAXIMS IN FICTION TRANSLATION: NEW INSIGHTS INTO COOPERATION, CHARACTERIZATION, AND STYLE - Abualadas, Othman Ahmad (Indonesian Journal of Applied Linguistics, 2020)
This paper analyses Grice?s maxims in two Arabic translations of Animal Farm to gain insight into the communicative principles underlying character-to-character, narrator-to-reader, and translator-to-reader interactions in fiction translation. Compared to the original, the translated character-level interactions show more frequent use of maxim hedges, more awareness of or commitment to maxims, more informative responses, and more manifestations of interpersonal relationships, politeness and propositional attitudes. They also show a preference for observing rather than flouting maxims and hence for explicating rather than implicating a meaning. By contrast, there are fewer narrator-reader implicatures, reduced persuasive power and hence a lesser reader engagement. The overall results point to a higher level of explicitness and informativeness that contributes to the conciseness and simplicity of the translational language and style. Compared to the original writer, translators provide more contextual knowledge and show more awareness of conversational maxims during the re-narration and mediation process.